Trial excavations of a Neolithic site in Islam Grčki (In situ, 2024)
The Department of Archeology of the University of Zadar conducted archaeological trial trenching at the site of Graduša - Lokve in Islam Grčki in 2022 where numerous archaeological finds attributed to the Middle and Late Neolithic were collected on the surface of this site in the 1960s and 1970s. Archaeological trial trenching was undertaken with the aim of determining the potential of the Neolithic site for future systematic archaeological research.
Keywords: Islam Grčki; Neolithic; Danilo culture; Hvar culture